SYNTACTIC AND SEMANTIC FEATURES OF NEGATIVE STATEMENTS IN ENGLISH AND THEIR VIETNAMESE EQUIVALENTS / Nguyễn Thu Hương; NHDKH Dr Đặng Ngọc Hướng - Nguyễn, Thu Hương
The purpose of this study is to investigate the syntactic and semantics features of English negative statements and their Vietnamese equivalents at phrase level. Sample data in this study is mainly taken from the book “The world is flat” together with the novel “The old man and the sea” by Ernest Hemingway and the English-Vietnamese Dictionary by Ho Chi Minh Publishing House (1993 edition). The study is aimed at three point: (1) to clarify syntactic and semantics features of English negative statements and their Vietnamese equivalents, (2) finding the similarities and differences between negative statements in English and in Vietnamese and (3) providing some recommendation for the teaching and learning of English negative statements to Vietnamese learners and teachers.This study was designed as a descriptive research with the method of contrastive and componential analysis. After analyze all of the data avialble, result of the study show that English negative statements at phrase level are diverse in structure and the way they convey the negative meaning are vary. On the other hand, the negative meaning presented in Vietnamese negative statement are brought about by negative word “không” in a vast number of cases. The word “không” is unlimited in term of useage, it can negate for noun, verb, subject, objects, … In general, the meaning of negative statements in English and their Vietnamese equivalents are almost the same in most of the cases. This would be the point where learning English is easier for Vietnamese. There are still learning and teaching difficulties created by difference in syntax. To overcome these difficulties, teachers and Vietnamese learners of English may take advatanges of several recommendation metioned in Chapter 4 of this thesis.